2017
DOI: 10.1371/journal.pone.0178169
|View full text |Cite
|
Sign up to set email alerts
|

Whole-genome sequencing of spermatocytic tumors provides insights into the mutational processes operating in the male germline

Abstract: Adult male germline stem cells (spermatogonia) proliferate by mitosis and, after puberty, generate spermatocytes that undertake meiosis to produce haploid spermatozoa. Germ cells are under evolutionary constraint to curtail mutations and maintain genome integrity. Despite constant turnover, spermatogonia very rarely form tumors, so-called spermatocytic tumors (SpT). In line with the previous identification of FGFR3 and HRAS selfish mutations in a subset of cases, candidate gene screening of 29 SpTs identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 72 publications
(155 reference statements)
2
36
0
Order By: Relevance
“…TGCC carried low numbers of SNV (~0.1 per Mb, Fig. 1B), somewhat lower than reported previously [12][13][14] and comparable to some of the pediatric cancers and spermatocytic tumors 28,30 . The total number of SNV with a predicted impact on the encoded protein (3 -16, Table 1) was similar to other reports [11][12][13] .…”
Section: Discussionsupporting
confidence: 45%
“…TGCC carried low numbers of SNV (~0.1 per Mb, Fig. 1B), somewhat lower than reported previously [12][13][14] and comparable to some of the pediatric cancers and spermatocytic tumors 28,30 . The total number of SNV with a predicted impact on the encoded protein (3 -16, Table 1) was similar to other reports [11][12][13] .…”
Section: Discussionsupporting
confidence: 45%
“…This would represent a mechanism by which the testis "filters" the transmission of pathogenic mutations across generations, although proof of this concept would require the development of ultrasensitive assays to screen large numbers of sperm samples. It is noteworthy that despite the relative abundance of strongly oncogenic mutations in the adult male germline, testicular tumors originating from adult spermatogonia (spermatocytic tumors) are extremely rare, with an incidence of about one per million men and are mostly benign in nature (Ghazarian et al 2015;Giannoulatou et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms underlying GCNIS establishment and progression into either subtype are largely obscure, particularly because this process may take years to decades. Genome-wide association studies (GWAS) have most frequently identified KITL and KRAS alleles as the highest genetic risk factor ( 81 ), providing clues to processes or events that may enable inappropriate survival of germ cells that do not differentiate. Mice and other common laboratory animals do not develop TGCTs similar to those found in humans; the timespan from PGC formation to onset of spermatogenesis in a mouse is less than one month, while in humans this transformation typically lasts several years.…”
Section: Cytokines In Testicular Pathologiesmentioning
confidence: 99%